Sanksi Hukum Anak Yang Membunuh Ibu Tirinya Dalam Perspektif Hukum Pidana Islam Dan Hukum Pidana : ( Studi Putusan Nomor 823/Pid.B/2019/PN Kis ) - Nur Kemala Dewi Lubis; M. Rizal; Syaddan Dintara Lubis (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This research discusses the legal sanctions for children who kill their stepmother which occurred in Pulo Bandring District, Asahan Regency. This research will analyze the Kisaran District Court Decision Number.823/Pid.B/2019/PN.Kis, which aims 1. To find out what the provisions are for legal sanctions for children who kill their stepmother from a criminal law perspective, 2. What are the provisions for legal sanctions for children who killing his stepmother according to the perspective of Islamic criminal law, and 3. What are the legal considerations of the judge in making a decision regarding the child who killed his stepmother (Decision Study Number.823/Pid.B/2019/PN.Kis). This research uses Normative Law, which is research that examines document studies, namely using legal source materials. The results of the research in this study are: 1. A person can be said to be the perpetrator of the crime of murder and has fulfilled the elements of the crime of murder, and has been proven to have committed the crime of murder with supporting evidence, which states clearly that the person has committed the crime. criminal act of murder. 2. Not only criminal law, Islamic criminal law also regulates sanctions for perpetrators of criminal acts of murder. The crime of murder by intentionally taking another person's life in Islamic criminal law is categorized as Al-Qatlu. 3. When formulating a case, a judge must first consider the creation of fair law in society. In Decision No. 823/Pid.B/2019/PN.KIS in considering the law the judge made a decision using alternative charges. Although the alternative indictment consists of several layers, only one will be proven. Proof does not need to be carried out sequentially according to the layers, but directly to what is deemed proven. Because Article 338 of the Criminal Code has been clearly proven, based on the element of who and the element of intentionally taking another person's life, then in decision No. 823/Pid/B/2019/PN.KIS the judge decided that the defendant was caught in the second alternative charge, namely Article 338 of the Criminal Code, namely intentional murder, to which evidence was attached which was obtained at the scene of the crime. So the judge decided that the defendant was subject to imprisonment for 10 (ten) years.